Revenue and expenditure nexus: A case study of Romania - Qazi Muhammad Adnan; Anwar Jalil (Romanian Journal of Fiscal Policy (RJFP), 2010)
This study determines the causal relationship between the expenditure and revenue of government in the case of Romania by using the autoregressive distributive lag approach to cointegration, variance decomposition and rolling regression method. The results indicate that bidirectional long run relationship exist between expenditure and revenue of government. The variance decomposition method suggests government revenue shock has more sharply impact on the government expenditure as compared to the shock in government expenditure and response of government revenue collection.
Keywords: E62; C4; 330; government revenue; government expenditure; cointegration